PERLINDUNGAN HUKUM TERHADAP AKSES DAN PEMANFAATAN SUMBER DAYA GENETIK - Djaya, Hendra (Jurnal Cakrawala Hukum, 2017)
Indonesia do not have the legal system comprehensive national in connection with the protection of geneticresources.The current law, still in cutting and or partial effective if problems linked to maintain the law.Thestate of having of absolute right to protect wealth of biodiversity in which includes genetic resources.With theratification of various international convention such as GATT, TRIPS, WTO, CBD, Cartagena and NagoyaProtocol,Indonesia bound to implement the through national law.Protection of genetic resources, associated with two legal concept that: (1), legal concept protection intellectualproperty right and; (2) Legal concept protection germ plasm especially genetic resources plants.The differenceis that the protection of intellectual property associated with genetic resources, is disliked exclusive rights forexample, the Plant Variety Protection and Patent. While the protection of access and the utilization of geneticresources is disliked communal on the use of farmers tardisional of genetic resources is not exclusive.That access to resources genetic run well, we need to by controlling the maximum as the provisions of the act ofact number 11 of 2013 regarding the ratification of the Nagoya Protocol. That the purpose of the effectivenessof the protection of genetic resources in the future reach goodness in the process of legislation, harmonizationgood law principle and a norm law need to be carried out optimally. Several points important that needattention, among others, about standard funds, substance agreement diversion genetic material, percentageshare of the profits, protection intellectual property as well as institutions supervision.